Upaya Meningkatkan Kebiasaan Belajar Terhadap Prestasi Belajar Siswa Melalui Layanan Bimbingan Kelompok Dengan Teknik Self Management di MTs Muslimat NU Palangka Raya - Wibisono, Muhammad; Idha, Sunaryo; Sangalang, Oktamia (Jurnal Bimbingan dan Konseling Pandohop, 2021)
This study aims to determine the effectiveness of group guidance self-management techniques in improving study habits on learning achievement. This type of research is experimental research. The data collection technique used a study habits questionnaire with a Likert scale and Legger documents from the value of learning achievement results carried out in 2 (two) meetings. The data analysis technique used paired T-test. The number of research samples is 10 (ten) students. The sampling technique in this study was done by purposive sampling. And the calculation of the results using the pre-test and post-test one group design. Based on the results of the research that has been carried out, the results obtained from the use of group guidance through group guidance services with self-management techniques before being given treatment, the results of the pretest average score of 50 after being given treatment changed to 68.5 with an increase of 18.5. As for the value of learning achievement results before being given treatment, the average value of the legger pretest was 70.1 after being given treatment, it changed to 76.46 with an increase of 6.36. This proves that there is an increase between the pretest and posttest. From the results of the research that has been done and the results of hypothesis testing, the error rate is 5% if t count < t table db n-1, it is known that tcount of study habits is -9.6214 and ttable is 2.262. This means that tcount > ttable, Ho is rejected and Ha¬ is accepted, so it can be concluded that group guidance using self-management techniques is effective in improving study habits on student achievement in class IX-B MTs Muslimat NU Palangka Raya.